2023
DOI: 10.4097/kja.22491
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality simulator’s effectiveness on the spine procedure education for trainee: a randomized controlled trial

Abstract: This article has been accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…[60] In one RCT involving a Unity-based immersive VR simulator, trainees learning lumbar transforaminal epidural block placement using VR outperformed those who learned via text and video material alone. [58]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[60] In one RCT involving a Unity-based immersive VR simulator, trainees learning lumbar transforaminal epidural block placement using VR outperformed those who learned via text and video material alone. [58]…”
Section: Resultsmentioning
confidence: 99%
“…[60] In one RCT involving a Unity-based immersive VR simulator, trainees learning lumbar transforaminal epidural block placement using VR outperformed those who learned via text and video material alone. [58] Although software like Unity has reduced the redundant work in the development of XR education and simulation software, there is significant heterogeneity in how individual systems are developed. Lampotang et al argue that these heterogeneous approaches may lead to increased validation and curriculum development costs.…”
Section: Educational Applications Of Extended Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…The simulator was developed using a process similar to that used for our previous spinal procedure simulator. 14 However, considering that the SCS procedure is usually performed on the cervical or thoracic spine, the CT data of the entire spine were used in this study. As with the previous simulator, real-time virtual X-rays could be generated by matching the patient’s Digital Imaging and Communications in Medicine data coordinates, Hounsfield unit values, and virtual objects in the virtual spaces.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, VR simulators have emerged as an alternative to traditional educational methods, particularly given the recently established guidelines for minimizing physical contact. A study by Kim et al [ 8 ] found that using a VR simulator in spinal procedure education resulted in higher global rating scores, reduced procedural times, reduced use of C-arms, and higher overall satisfaction scores, supporting the use of VR simulators as teaching aids compared to self-learning groups using video and book.…”
mentioning
confidence: 99%